Tratamiento de la Información sobre violencia de género en las cuentas de Tiktok de los medios digitales en el Ecuador: Caso Letty Cando - Cadena Bonilla, Daniela Estefania (2024)
The research on the treatment of information on gender violence in TikTok accounts of digital media in Ecuador: Letty Cando case, studies the problem in the way of media approach to publications (TikToks) in the public perception and violation of the rights of the victim. Using the mixed paradigm, the methodology combines the techniques of quantitative content analysis and qualitative discourse analysis of 82 videos published in September 2023 to January 2024. This research examines the interactivity, content, authorship, multimedia resources, copies, sources, narration of the facts, and rates of violation of rights of the content disseminated by Ecuadorian digital media through TikTok. The study was weighed with interviews with communication and legal professionals. The results show a predominance of sensationalism, with an emphasis on graphic and emotional details that desensitize audiences and perpetuate negative stereotypes. The case of Lety Cando generated a high virality\; however, the interactivity of users was limited, reflecting a passive consumption of information on the digital platform.